2002
DOI: 10.1046/j.0019-2805.2001.01358.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in MHC class II antigen presentation

Abstract: Summary Processing exogenous and endogenous proteins for presentation by major histocompatibility complex (MHC) molecules to T cells is the defining function of antigen‐presenting cells (APC) as major regulatory cells in the acquired immune response. MHC class II‐restricted antigen presentation to CD4 T cells is achieved by an essentially common pathway that is subject to variation with regard to the location and extent of degradation of protein antigens and the site of peptide binding to MHC class II molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
89
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 131 publications
1
89
0
Order By: Relevance
“…We, 26,59 and others (reviewed in ref. 60), have previously shown that the intracellular origin of the MHC class II molecules used to form peptide-MHC complexes can profoundly influence subsequent CD4 + T cell activation. Therefore we compared the intracellular origins of the MHC class II molecules in aggrecan-specific B cells, macrophages and DC that were involved in the presentation of the p84-103 epitope.…”
Section: Discussionmentioning
confidence: 99%
“…We, 26,59 and others (reviewed in ref. 60), have previously shown that the intracellular origin of the MHC class II molecules used to form peptide-MHC complexes can profoundly influence subsequent CD4 + T cell activation. Therefore we compared the intracellular origins of the MHC class II molecules in aggrecan-specific B cells, macrophages and DC that were involved in the presentation of the p84-103 epitope.…”
Section: Discussionmentioning
confidence: 99%
“…Role of Endosome Acidification in Antigen Presentation of rPA-Progress of endocytosed antigens from early endosomes to the low pH environment of late endosomes or lysosomes is required for presentation of many (17) but not all (24,42,43) CD4 ϩ T-cell epitopes. Macrophages were treated with NH 4 Cl, a weak base that raises endosomal pH (44) to determine whether a low pH is required for presentation of each of the PA epitopes.…”
Section: Kinetics Of Presentation Of Pa Epitopes By Macrophages-mentioning
confidence: 99%
“…ϩ T-cells are liberated from protein antigens following some form of antigen processing before they are accessible to bind MHC class II molecules usually in acidic endocytic compartments of antigen presenting cells (APC) such as macrophages, dendritic cells, and B cells (17)(18)(19)(20)(21)(22)(23)(24). Following uptake by APC, processing is thought to be initiated during transport through the endosomal system by unfolding of antigens induced by low pH (25,26), oxidation (27), disulphide reduction (28 -30), or limited cleavage by lysosomal enzymes such as asparaginyl endopeptidase (31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is increasingly apparent from studies using pathogenderived antigens that use of the recycling MHC class II pathway may be more prevalent than originally predicted (reviewed in [27]). It is therefore likely that our finding may have wider implications for antigen presentation.…”
Section: A Model For Enhanced Presentation Of Certain T Cell Epitopesmentioning
confidence: 99%